2020
DOI: 10.1017/s1479262120000179
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the morphological diversity of tea roses (Rosa x odorata) based on phenotypic traits

Abstract: Rosa x odorata (sect. Chinenses, Rosaceae) is an important species distributed only in Yunnan Province, China. There is an abundance of wild variation within the species. Using 22 germplasm resources collected from the wild, as well as R. chinensis var. spontanea, R. chinensis ‘Old Blush’ and R. lucidissima, this study involved morphological variation analysis, inter-trait correlation analysis, principal component analysis and clustering analysis based on 16 morphological traits. This study identified a high d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The larger the coefficient of variation of the trait, the greater the dispersion degree of the trait, indicating that the genetic background of the trait is richer, and that the selection space during breeding is also greater. On the contrary, the smaller the coefficient of variation, the smaller the discrete degree of the trait is, indicating that the stability of the trait is better [35]. The previous results of fruit quality determination and variation analysis of wild A. eriantha germplasm resources showed that the coefficients of variation among different fruit traits were quite different [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…The larger the coefficient of variation of the trait, the greater the dispersion degree of the trait, indicating that the genetic background of the trait is richer, and that the selection space during breeding is also greater. On the contrary, the smaller the coefficient of variation, the smaller the discrete degree of the trait is, indicating that the stability of the trait is better [35]. The previous results of fruit quality determination and variation analysis of wild A. eriantha germplasm resources showed that the coefficients of variation among different fruit traits were quite different [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Tea-scented roses, belonging to the genus Rosa in the family Rosaceae, are naturally distributed in Yunnan, China. 22,23 Located near the equator, Yunnan enjoys a warm and humid climate with diverse topography, including mountains, hills, basins, and valleys. This provides an excellent growth habitat for various roses, 24 including tea-scented roses, which enables researchers to gain a better understanding of their ecological characteristics, adaptability, and potential medicinal value, thus providing a scientific basis for their conservation and utilization.…”
Section: Introductionmentioning
confidence: 99%
“…23 Apart from their potential as materials for fragrance research and breeding, tea-scented roses also produce unique fruits. Compared to common rosehips such as R. canina and R. rugosa, tea-scented roses have both larger plants and larger flowers, 22 resulting in larger and more numerous fruits with a greater edible yield. The strong floral aroma of tea-scented roses also suggests that certain bioactive components in their flowers may also be found in their fruits, 25 enhancing the nutritional value of the rosehips and making them a potential source of functional foods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation